Optimalisasi penerapan model pembelajaran preskriptif untuk meningkatkan aktivitas belajar geografi siswa SMAN 2 Denpasar - Erdina Mery Krismawati (Indonesian Journal of Educational Development, 2021)
This study aims to determine the increase in learning activities and geography learning achievement of students in class X IPS 1 semester 2 of the 2019/2020 academic year at SMA Negeri 2 Denpasar after applying the Prescriptive learning model. This type of research is PTK which consists of two cycles with the subject of 43 students in class X IPS 1 SMA Negeri 2 Denpasar in the 2019/2020 school year. Student data were obtained through observation sheets and achievement tests for learning outcomes which were analyzed using descriptive analysis. The application of the prescriptive learning model can increase students' geography learning activities. It can be seen from the achievement of the average score of student learning activities in the first cycle of 8.32, increasing to 11.72 in the second cycle. In addition, the application of the prescriptive learning model also improves students' learning achievement in geography as seen from the increase in the average score of student learning achievement in the first cycle of 62.56 to 72.09 in the second cycle, the increase in student absorption from 62.56% in the cycle. I became 72.09% in the second cycle and the classical learning completeness increased from 13.95% in the first cycle to 62.79% in the second cycle. Penelitian ini bertujuan untuk mengetahui peningkatkan aktivitas belajar dan prestasi belajar geografi siswa kelas X IPS 1 semester 2 tahun pelajaran 2019/2020 di SMA Negeri 2 Denpasar setelah diterapkan model pembelajaran Preskriptif. Jenis penelitian ini adalah PTK yang terdiri dari dua siklus dengan subjek siswa kelas X IPS 1 SMA Negeri 2 Denpasar pada tahun pelajaran 2019/2020 sebanyak 43 orang siswa. Data siswa diperoleh melalui lembar observasi dan tes prestasi hasil belajar yang dianalisis menggunakan analisis deskriptif. Penerapan model pembelajaran preskriptif dapat meningkatkan aktivitas belajar geografi siswa dapat dilihat dari pencapaian skor rata-rata aktivitas belajar siswa pada siklus I sebesar 8,32 meningkat menjadi 11,72 pada siklus II. Selain itu dengan penerapan model pembelajaran preskriptif juga meningkatkan prestasi belajar geografi siswa dilihat dari peningkatan nilai rata-rata prestasi belajar geografi siswa pada siklus I sebesar 62,56 menjadi 72,09 pada siklus II, peningkatan daya serap siswa dari 62,56% pada siklus I menjadi 72,09% pada siklus II dan peningkatan ketuntasan belajar secara klasikal 13,95 % pada siklus I menjadi 62,79% pada siklus II.